2013
DOI: 10.1007/s10802-013-9840-y
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Victimization-Related Beliefs and Strategies: Associations with Students’ Aggressive Behavior and Peer Victimization

Abstract: Although teachers are often called upon to reduce children's bullying and aggression, little is known regarding teachers' responses to students' harassment of peers or the beliefs which may inform their response strategies. To address this limitation, data were collected from 170 6th- and 7th-grade teachers (33 men; 137 women) and 2,938 (1,413 girls; 1,525 boys) of their students. Teachers beliefs regarding peer victimization were predictive of their efforts to advice victims how to cope with peer harassment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
148
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 40 publications
7
148
1
13
Order By: Relevance
“…While permissiveness favors the empowerment of the aggressor, increasing the vulnerability of victims. Direct intervention practices have the opposite effect, reducing the instrumental and affective gains of the aggressors and empowering the victims (James et al, 2008;Troop -Gordon & Ladd, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While permissiveness favors the empowerment of the aggressor, increasing the vulnerability of victims. Direct intervention practices have the opposite effect, reducing the instrumental and affective gains of the aggressors and empowering the victims (James et al, 2008;Troop -Gordon & Ladd, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Teaching practices send an implicit message to students about the extent to which teacher approves or disapproves of this behavior (Troop-Gordon & Ladd, 2013, Yoon, 2004. Teachers' responses that are perceived by their students as approving victimization, whether or not the teacher's intention, increase the frequency and intensity of the phenomenon (Bauman & Del Río, 2006;Byers, Caltabiano, & Caltabiano, 2011;Yoon, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some teachers understanding of bullying may be low, individual personalities must also be considered Research from Bauman and Del Rio (2006) finds that teachers had the least empathy for the victims of relational bullying over physical and verbal bullying, and were least likely to intervene in relational bullying incidents. Apart from a lack of knowledge about bullying, variations in teacher responses may also reflect teachers' a lack of empathy (Troop-Gordon & Ladd, 2015). Teachers with empathy will take time to understand students' behaviours and manage appropriately.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, surveys have shown that inadequate teacher training about tackling school bullying effectively is an important factor in enhancing victimization (Mishna, Scarcello, Pepler, & Wiener, 2005;Beran, 2006). It is therefore necessary to provide more advanced training, including various methods of intervention and knowledge of the appropriate selection and implementation of such interventions (Troop -Gordon & Ladd, 2015).…”
Section: Teachers' Responsibilitymentioning
confidence: 99%